Competitive analysis with diamond model in TR81 nuts 2 region forest products industry - Karayılmazlar, Selman; Uzcan, Gülay Şener; Karayılmazlar, Selman (Bartın Üniversitesi, 2016)
Developments in information and communication technologies gaining momentum with globalization have influenced economies' business manners and policies significantly. The economies which are able to transform into innovative, information-based and value-added production structure and marketing strategies can be important business actors that are competing in global market. Competitive relationships have been studied at the level of country, region and business. The ideal scale that explains competitive relationships which play an important role in constituting competitive advantage is at the level of regional industries. For this reason, when competitive advantage is considered, we encounter with sectors that have been successful in certain regions and site-specific conditions bring success. Accordingly, TR81 NUTS 2 Region Forest Products Industry business cluster's competitive advantage has been analysed with the help of Michael Porter's diamond model. In order to collect data, complete inventory method has been used by applying surveys to 65 forest product businesses that were specified in the cities Zonguldak, Karabuk, and Bartın. With the business cluster competitive analysis, cluster's competitive advantages and disadvantages have been addressed.  In addition, shortcomings and possible solutions to develop the cluster and to increase its competitive advantage have been stated in the sections of conclusion and suggestions. It is estimated that this study can make a significant contribution to studies and regional projections to develop competitiveness of “TR81 region furniture and wood sector”.

Küreselleşme ile ivme kazanan bilgi ve iletişim teknolojilerindeki gelişmeler, ekonomilerin iş yapma biçimlerini ve politikalarını önemli ölçüde etkilemiştir. Yenilikçi, bilgiye dayalı ve yüksek katma değerli üretim ve pazarlama stratejilerine geçebilenler küresel rekabette önemli aktörler olabilecektir. Rekabet ilişkileri ülke, bölge ve işletme düzeyinde incelenmektedir. Ancak rekabet gücünün oluşmasında rol oynayan rekabet ilişkilerini en iyi açıklayan ölçek bölgesel endüstriler düzeyinde olanıdır. Çünkü rekabet gücü söz konusu olduğunda, belli bölgelerde başarılı olmuş sektörler karşımıza çıkmakta ve bölgeye özel koşullar başarıyı getirmektedir. Bu amaçla TR81 Düzey 2 Bölgesi Orman Ürünleri Endüstrisi iş kümelenmesinin rekabet gücü Michael Porter'ın karo modeline göre analiz edilmiştir. Uygulamada veri toplamak amacı ile tam sayım tekniği kullanılarak Zonguldak, Karabük ve Bartın illerinde belirlenen 65 adet orman ürünleri endüstri işletmesine anket uygulanmıştır.  İş kümelenmesi rekabet analizi ile kümelenmenin rekabetçi avantajları ve dezavantajları üzerinde saptamalarda bulunulmuş, kümelenmeyi geliştirmek ve rekabet gücünü artırabilmek için eksiklerin neler olduğu, neler yapılabileceği sonuç ve önerilerde ifade edilmiştir. Bu çalışmanın, “TR81 bölgesi mobilya ve kereste sektörünün” rekabetçiliğini geliştirmek için yapılacak çalışmalara ve bölgesel planlara katkı sunacağı öngörülmüştür.
TR81 Düzey 2 Bölgesi Orman Ürünleri Endüstrisinde Karo Modeli İle Rekabet Analizi